Brief conceptual review on the evaluation of academic results in the educational system (Revista Científica Estelí, 2021)
In this documentary review article, a theoretical study of evaluation in education was carried out. The main sources consulted were books, journal articles. There are several definitions, functions and practices in evaluation that have generated debates throughout history and are still in force in educational system. In this article, some assessment concepts, characteristics, modalities and paradigms are included. It considers the elaboration of the academic performance report as a feedback tool for the analysis of the aspects of the educational activity that were satisfactory and need to be strengthened and those that need to be modified. It is an attempt to expand the view of the classroom evaluation, based on academic performance, which allow transforming the evaluative practice implemented by teachers. In order to give continuity to these results, it is not limited only to the measurement process for the purpose of accreditation of the academic semester or promotion of academic year. This implies, stablishing strategies and actions for continuous improvement in the educational process for the benefit of students learning, based on the critical analysis of the academic results.
Keywords: Evaluation; learning; academic performance